Ethics and Science in Philosophy: Understanding the Nature of Science in an Educational Context - Syifa, Nahdli Muhammad Nur; Husnaini, M.; Harimurti, Shubhi Mahmashony (International Journal of Asian Education, 2024)
This study aims to explore the crucial relationship between ethics and science within a philosophical framework, with a specific emphasis on understanding the nature of science in the context of education. The research addresses fundamental questions about how ethics influences and shapes the role of scientific knowledge in the educational process. Examining the concepts of ethics and science from a philosophical perspective, this study presents an in-depth analysis of their interconnectedness and philosophical significance. The significance of ethics in science, particularly in education, is the primary objective identified as a moral foundation guiding the development and utilization of scientific knowledge. In this context, the researcher employed a literature review method. The study proposes efforts to comprehend the nature of science as an integral part of student's character development and understanding of the world. These efforts include critically reflecting on the ethical values embedded in scientific knowledge and emphasizing the integration of ethics into forming worldviews. Taking a philosophical approach, this research delineates the conceptual and practical implications of the relationship between ethics and science, providing a foundation for holistic thinking. The conclusion of this research suggests the development of educational methods and strategies that consider ethics as a central element in the knowledge transmission process. The study is expected to contribute positively to strengthening the balance between ethics and science in future generations' education, fostering intellectual intelligence and ethical and social integrity.